Respostas

  • Usuário do Brainly
2013-01-10T20:17:33-02:00

Temos a equação:

 

(\text{A}+1)\cdot\text{x}=2

 

a)

 

Se \text{A}=1, tém-se:

 

(1+1)\cdot\text{x}=2

 

2\text{x}=2

 

\text{x}=1

 

b)

 

Como \text{A}=-1, temos:

 

(-1+1)\cdot\text{x}=2

 

0\cdot\text{x}=2

 

\text{x}=\emptyset

 

c)

 

A solução geral é definida como segue:

 

(\text{A}+1)\cdot\text{x}=2

 

\text{A}\cdot\text{x}+\text{x}=2

 

Colocando em evidência \text{x}, obtemos:

 

\text{x}\cdot(\text{A}+1)=2

 

Donde, segue:

 

\text{x}=\text{A}+1